1996
DOI: 10.1111/j.1365-2672.1996.tb04336.x
|View full text |Cite
|
Sign up to set email alerts
|

Note: Influence of different heating media on thermal resistance of Neosartorya fischeri isolated from papaya fruit

Abstract: E. RAJASHEKHARA, E.R. SURESH AND s. ETHIRAJ. 1996. A heat-resistant mold identified as a strain of Neosartorya jischeri was isolated from microbiologically spoiled papaya fruits. The optimum heat activation temperature and time for the ascospores of the test mold was found to be 80°C for 15-30 min. The decimal reduction times (D-values) at 85", 87" and 89°C in phosphate buffer (pH 7.0) as heating medium were 35.25, 11.1 and 3.90 min respectively and hence the calculated z-value was 4.0"C. In grape and mango ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 16 publications
2
13
0
2
Order By: Relevance
“…Beuchat (1986) also observed N. fischeri FRR 1833, FRR 2334, and FRR 110483 ascospore activation up to 4.5 logs in buffer by 75 and 80 C thermal processes during the first 15e45 min. Other investigators reported lower spore activation (0.25e0.8 log) between 10 and 50 min with N. fischeri (E7, C3, and isolated from spoiled papaya fruit) spores in buffer at the same temperatures which is similar to our results (Amaeze & Ugwuanyi, 2011;Rajashekhara, Suresh, & Ethiraj, 1996). Slongo and Aragão (2006) found that temperature of 85 C between 10 and 20 min was required for maximum activation of N. fischeri ascospores in pineapple and papaya nectar, however the level of activated spores was not mentioned.…”
Section: Ascospore Activation and Activation Shoulderssupporting
confidence: 94%
See 1 more Smart Citation
“…Beuchat (1986) also observed N. fischeri FRR 1833, FRR 2334, and FRR 110483 ascospore activation up to 4.5 logs in buffer by 75 and 80 C thermal processes during the first 15e45 min. Other investigators reported lower spore activation (0.25e0.8 log) between 10 and 50 min with N. fischeri (E7, C3, and isolated from spoiled papaya fruit) spores in buffer at the same temperatures which is similar to our results (Amaeze & Ugwuanyi, 2011;Rajashekhara, Suresh, & Ethiraj, 1996). Slongo and Aragão (2006) found that temperature of 85 C between 10 and 20 min was required for maximum activation of N. fischeri ascospores in pineapple and papaya nectar, however the level of activated spores was not mentioned.…”
Section: Ascospore Activation and Activation Shoulderssupporting
confidence: 94%
“…The Weibull model has been used by Sant'Ana et al (2010) for the thermal inactivation of Byssochlamys fulva ascospores in apple juice. The majority of previous thermal studies found nonlinearities for N. fischeri log survivors (Beuchat, 1986;Kotzekidou, 1997;Rajashekhara et al, 1996;Salomão, Slongo, & Aragão, 2007), but used first order or linearized first order model proposed by Alderton & Snell (1970) to estimate the kinetic parameters. Although the error is higher and fitting not so good (0.924 R 2 , 0.365 MSE, 1.27 A f ), the first order D 90 C of 4.9 min was also determined to be able to compare with past results.…”
Section: Modeling the Ts Inactivation Of N Fischeri Ascospores In Apmentioning
confidence: 99%
“…Spoilage by heat-resistant fungi is a major problem for fruit-processing industries and has been documented in many countries (Baglioni, Gumerato, & Massaguer, 1999;Kotzekidou, 1997;Obeta & Ugwuanyi, 1995;Rajashekhara, Suresh, & Ethiraj, 1996;Suresh, Ethiraj, & Jayaram, 1996). Contamination of processed fruits by fungi originates in fields and orchards, where the fungi have been isolated (Tournas, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, the occurrence of deterioration episodes (Olliver and Rendle 1934;Obeta and Ugwuanyi 1995;Rajashekhara et al 1996;Suresh et al 1996;Kotzekidou 1997;Baglioni et al 1999) indicates that the stage to which microbiological stability and safety of the fruit juices (pasteurization) is attributed, may not, on its own, be efficient in reducing ⁄ eliminating even low loads of these contaminants. This can be due to the elevated heat resistance of mould ascospores (Tournas 1994) or to log-linear kinetics behaviour followed by some micro-organisms.…”
mentioning
confidence: 99%